Women in Rheumatology in the Arab League of Associations for Rheumatology Countries: A Rising Workforce - Ziade, Nelly; Hmamouchi, Ihsane; El Kibbi, Lina (Frontiers in Medicine, 2022)
Background An increase in women physicians in the medical workforce is witnessed in recent decades, paralleled by an increase in leadership positions and, to a lesser extent, in academic advancement. Objectives This study aims to evaluate the women rheumatologists (WR) workforce and to identify the challenges faced by WR in the Arab League of Associations for Rheumatology (ArLAR) countries. Methods We collected data from members of special interest groups from 16 ArLAR countries about the number of rheumatologists in the national societies and boards – including WR –, and the estimated percentage of WR involved in academia. Also, a sample of WR was identified based on their established leadership positions and invited to a structured interview addressing their career path and the gender-related challenges. Results The proportion of WR varied widely across the ArLAR countries, with a mean of 56%. Moreover, WR constituted 47% of the society’s board members and roughly 49% of WR were involved in academia. However, only 37% of the current society presidents were females. Structured interviews indicated that WR place a high value on patient care and teaching, followed by research and publications. The primary reported gender-related challenge was balancing work with family demands. Moreover, some WR reported gender-related discrimination incurred by colleagues, patients, and administrations. Conclusion WR constituted more than half of the current rheumatology workforce in the ArLAR countries, with a lower – but steadily growing – proportion of WR in leadership positions. As they embrace their growing role in the workforce, WR must benefit from all the provided tools, from learning from the experience of current women leaders in the field to using the latest technology such as social media platforms to empower them to reach gender equity.